Retorika dan Power Relations: Strategi Restorasi Citra Kepolisian Republik Indonesia pada Kasus Ferdy Sambo - Inri Inggrit Indrayani (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2022)
This research aimed to identify Indonesian National Police (Polri) strategy in carrying out image restoration in the Ferdy Sambo case. The case of Ferdy Sambo attracted substantial public attention throughout the end of 2022 because it involved members of the National Police in criminal acts. This incident undermined the image and reputation of the National Police as a state apparatus whose function is to maintain security and order. Furthermore, the case of Ferdy Sambo has implications for a communication crisis along with reports in the media that involve many parties as sources so that it brings speculation on the image of the Police. A communication strategy to restore the image was required in crisis communication management, especially in the early period of the crisis in order to maintain the organization's reputation. This research used a qualitative approach with qualitative content analysis as the method. This study used William Benoit's strategy formulation as divided image restoration strategies into five categories: "Denial, Evading Responsibility, Reducing offensiveness of events, Corrective action, and Mortification". The findings showed that the Polri image restoration strategy at the beginning of the Ferdy Sambo case was reducing the offensiveness of the event which consisted of bolstering followed by corrective action, while the combination of strategies practice was bolstering, differentiation, compensation, and corrective action in the post-initial case. The image restoration strategy used in the clarification meeting with Commission III of the DPR RI was to assume the crisis as an accident, bolstering, corrective action and mortification. This study found another strategy in the data as the trait of the qualitative content analysis required interpretation, apart from the strategy described by Benoit, namely hierarchical power at the beginning of the crisis, authoritative support in the post-crisis beginning and continuous improvement in the clarification meeting with Commission III of the DPR RI. The organization's power relations with the public and stakeholders determine the rhetoric and various strategies in crisis communication.ABSTRAKPenelitian ini bertujuan untuk mengidentifikasi strategi Polri dalam melakukan restorasi citra pada kasus Ferdy Sambo. Kasus Ferdy Sambo menarik perhatian besar publik sepanjang akhir tahun 2022 karena melibatkan para anggota Polri dalam tindakan kriminalitas. Peristiwa ini meruntuhkan citra dan reputasi Polri sebagai aparat negara yang berfungsi menjaga keamanan dan ketertiban. Selain itu, kasus Ferdy Sambo berimplikasi pada krisis komunikasi seiring dengan perberitaan-pemberitaan di media yang melibatkan banyak pihak sebagai narasumber sehingga membawa spekulasi pada citra Polri. Strategi komunikasi untuk merestorasi citra dibutuhkan dalam manajemen komunikasi krisis terutama pada periode awal krisis guna menjaga reputasi organisasi.  Pendekatan yang digunakan dalam penelitian ini ialah kualitatif dengan metode analisis isi kualitatif. Penelitian ini menggunakan rumusan strategi William Benoit yang membagi strategi restorasi citra menjadi lima kategori: “Denial, Evading Responsibility, Reducing offensiveness of event, Corrective action dan Mortification”. Hasil penelitian menunjukkan bahwa strategi restorasi citra Polri pada awal kasus Ferdy Sambo ialah reducing offensiveness of event yang terdiri dari bolstering dan diikuti dengan corrective action sedangkan pada paska awal kasus, kombinasi strategi yang digunakan ialah bolstering, differentiation, compentation serta corrective action. Strategi restorasi citra yang digunakan dalam rapat kerja dengan Komisi III DPR RI ialah melihat krisis sebagai kecelakaan, bolstering, corrective action dan mortification. Sebagaimana penelitian analisis isi kualitatif yang bersifat melakukan interpretasi data, peneliti menemukan strategi lain dalam data, di luar strategi yang dipaparkan Benoit yaitu hierarchical power pada awal krisis, authoritative support pada paska awal krisis serta continuous improvement dalam rapat kerja dengan Komisi III DPR RI. Power relations organisasi dengan publik maupun stakeholder yang dihadapinya menentukan retorika dan variasi strategi dalam komunikasi krisis.